Robert P. Weller: Discovering Nature: Globalization and Environmental Culture in China and Taiwan. Cambridge: Cambridge University Press 2006. 189 sider. Illus. ISBN 0-521-54841-1 (pb). Pris: £15.99, $27.99. ISBN 0-521-83959-9 (hb). Pris: £40, $70. - Bunkenborg, Mikkel (Tidsskriftet Antropologi, 2005)
Intet resumé